Theranostic Nanoplatforms for MRSA Detection and Destruction from Whole Blood. (23rd September 2013) - Fan, Zhen; Khan, Sadia Afrin; Dai, Xuemei; Tchouwou, Christine; Lu, Yuefeng; Ray, Paresh Chandra
<x xml:space="preserve">Abstract</x> Bloodstream infection with methicillin‐resistant Staphylococcus aureus (MRSA) and other drug‐resistant bacteria kill several million people in the world every year. Detection of drug‐resistant bacteria in the blood stream is clinically important to save lives. Driven by this need, multifunctional theranostic nanoplatforms have been developed for simultaneous targeted imaging and multimodal photodestruction of MRSA in a whole‐blood sample. Experimental data for the whole‐blood sample spiked with MRSA show that the theranostic nanoplatform can be used for fluorescence imaging after magnetic separation even in a 10−5:1 ratio. A targeted photodynamic and photothermal combined treatment shows that the multimodal treatment regime can dramatically enhance the possibility of destroying MRSA in vitro. Therefore, our developed theranostic nanoplatform have a great potential as a fluorescent marker and as a light absorber for combined therapy in clinical settings. The possible mechanisms and operating principles are discussed for targeted imaging and combined therapeutic actions using theranostic nanoplatform.